Response of stomatal conductance, transpiration, and photosynthesis to light and CO2 for rice leaves with different appearance days - Lv, Yuping; Gu, Linhui; Man, Runze; Liu, Xiaoyin; Xu, Junzeng (Frontiers in Plant Science, 2024)
To investigate the dynamics of stomata, transpiration, and photosynthesis under varying light intensities and CO 2 conditions during leaf development, the light response and CO 2 response of stomatal conductance (g sw ), transpiration rate (T r ) and net photosynthetic rate (P n ) were conducted for rice leaves at different days after leaf emergence (DAE). The results showed that 1) As photosynthetically active radiation (PAR) increased, leaf g sw , T r and P n initially increased rapidly and linearly, followed by a more gradual rise to the maximum values, and then either stabilized or showed a declining trend. The maximum g sw , T r , and P n were smaller and occured earlier for old leaves than that for young leaves. The g sw , T r , and P n all exhibited a linear decreasing trend with increasing DAE, and the rate of decrease slowed down with the reduction in PAR. 2) As CO 2 concentration (C a ) increased, the g sw and T r decreased gradually to the stable minimum value, while the P n increased linearly and slowly up to the maximum, then kept stable or decreased. The g sw , T r and P n initially kept high and then decreased with the increase of DAE. These results contributed to understanding the dynamics in g sw , T r and P n during rice leaf growth and their responds to varied light and CO 2 concentration conditions, and provide mechanistic support for estimating dynamic evapotranspiration and net ecosystem productivity at field-scale and larger-scale in paddy field ecosystems through the upscaling of leaf-level stomatal conductance, transpiration and photosynthesis.